(untitled) (Baghdad Science Journal, 2005)
Twelve N-(6-sustirured benzothanol-2-y1) succinamic acids and 3-(6-substitted benzonathol-2-y1)-carbamoyl propionyl chloride were synthesized in good yields from reaction of benzonathol2-yl)